Злой дух Ямбуя: [повести] / Григорий Федосеев - Федосеев Григорий Анисимович (Сибириада, 2019)
Экземпляры: ф.4 (20200619) / Инвентарный номер: 765 / Цена: / Сис.шифр: 84(2Рос=411.2)6-4 / Авт.знак: Ф 33 / ГРНТИ: 17.82.31 / ББК: 84(2Рос=411.2)6-44